SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SISWA TELADAN SMA NEGERI 1 CIKARANG UTARA MENGGUNAKAN METODE AHP (Analytic Hierarchy Process) - Agra Sesar Ariadi Putra, (2022)
The process of selecting exemplary students is important for every school, especially in high schools, both public and private schools, this is done to make students who are selected to be exemplary students to be able to become role models in the school environment for other students. Currently, the obstacle in the selection process for exemplary students is using the manual method so that the results of the decisions are less objective. In assisting the process of selecting exemplary students, schools need a Decision Support System (SPK) to be able to make decisions more effectively, the decision support system method applied is AHP (Analytical Hierarchy Process), and the users of this system consist of, homeroom teacher, administrator business (Admin) and also the vice principal for student affairs. This system requires UML to describe a system, then the system will be designed with a web-based application model using PHP, and a database using MySQL. The results of this study conclude that the use of a Decision Support System in the process of determining exemplary students provides more objective results, therefore the school no longer has to use the manual method, in determining exemplary students.